Trabecular bone area and bone healing in spontaneously hypertensive rats: a histometric study - Marta Ferreira Bastos; Felipe Vilhena Brilhante; Joyce Pinho Bezerra; Carlos Alberto Silva; Poliana Mendes Duarte (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Clinical and experimental studies have demonstrated some negative effect of hypertension on bone mineral density. The aim of this study was to evaluate bone healing and trabecular bone area (TBA) in spontaneously hypertensive rats (SHR), a well-established model of essential hypertension, when compared to normotensive rats (NTR). A critical-size defect was surgically created in the right tibia of SHR (n = 12) and normotensive rats (NTR; n = 12), while the contralateral tibia was left intact. Eight days later, the animals were sacrificed and the specimens processed in order to obtain decalcified sections. The area of newly-formed bone (NB) within the defect of the right tibia and the TBA in the left tibia were histometrically evaluated. At 8 days post-operative, SHR presented a significantly smaller area of NB when compared to NTR (p < 0.05). In addition, SHR demonstrated a lower TBA than NTR group. In conclusion, the present study demonstrated that SHR rats presented a disturbed bone healing and reduced TBA.